The Making of Sami Ethnography: Contested Authorities and Negotiated Representations - Kristin Kuutma (Journal of Ethnology and Folkloristics)
This contribution analyzes the interplay of ethnographic and poetic agendas, the negotiation of synergetic or conflicting objectives in the production and editing of a seminal representation of the Sámi, Muitalus sámiid birra. My main focus is on the collaborative effort of the publication process, to investigate the emergence and negotiation of representational authority, of cultural poetics, of social and cultural critique, in order to defy the preconception of a passive informant of a cultural experience. The Sámi narrator Johan Turi is discussed, instead, as an active agent in providing a voice to the Sámi people in the collaborative process of ethnography writing. My approach is interdisciplinary, being inspired by different inquiries in anthropology and cultural history, while adding a subjective interpretation in discerning the production of a multifaceted ethnographic representation, both by the cultural insider and the inquisitive outsider.